Comparison of different pain management strategies during the perioperative period of esophageal squamous cell carcinoma: a retrospective cohort study - Yan Ma; Haiyan Wu; Xinqi Wei; Ying Yang; Zhiyun Xu; Yunyun Chen (Perioperative Medicine)
Abstract Objective This retrospective cohort study aims to evaluate and compare different postoperative pain management strategies for esophageal squamous cell carcinoma (ESCC), in order to provide scientific evidence for clinical practice and decision-making. Methods A total of 274 ESCC patients who underwent surgery at the Affiliated Huai’an No. 1 People’s Hospital of Nanjing Medical University were included in the study. Of these, 127 received conventional nursing decisions for postoperative pain management, and 147 received the “5 + nursing” postoperative pain management strategy. The main observation indicators of both groups included postoperative pain score, analgesic dosage, postoperative analgesic side effects, and length of hospital stays. Results The “5 + nursing” postoperative pain management group showed significantly lower postoperative pain score and significantly shorter length of hospital stays than the conventional nursing group. There was no significant difference in postoperative analgesic side effects between the two groups. Multiple logistic regression analysis showed that the postoperative pain score is an independent risk factor for predicting postoperative arrhythmias in ESCC patients. When the daily average dose of opioids used postoperatively was between 37.5 and 50 mg, the patient’s postoperative pain score dropped the fastest. Conclusion The “5 + nursing” pain management strategy can effectively reduce the degree of postoperative pain and shorten the length of hospital stays, improving patient’s quality of life. Our research emphasizes the importance of opioids in postoperative pain management, as well as the need for individualized perioperative pain management strategies.